Pandemic influenza A(H1N1)pdm09: An unrecognized cause of mortality in children in Pakistan. (October 2013) - Ali, Syed Asad; Aziz, Fatima; Akhtar, Nida; Qureshi, Shahida; Edwards, Kathryn; Zaidi, Anita
Abstract The role of influenza virus as a cause of child mortality in South Asia is under-recognized. We aimed to determine the incidence and case fatality rate of influenza A(H1N1)pdm09 infections in hospitalized children in Karachi, Pakistan. Children less than 5 y old admitted with respiratory illnesses to the Aga Khan University Hospital, Karachi, from 17 August 2009 to 16 September 2011, were tested for influenza A(H1N1)pdm09 using a real-time reverse transcriptase polymerase chain reaction. Out of 2650 children less than 5 y old admitted with a respiratory illness during the study period, 812 (31%) were enrolled. Influenza A(H1N1)pdm09 virus was detected in 27 (3.3%) children. There were 4 deaths in children who tested positive for influenza A(H1N1)pdm09 (case fatality rate of 15%). Children with influenza A(H1N1)pdm09 were 5 times more likely to be admitted or transferred to the intensive care unit, 5.5 times more likely to be intubated, and 12.9 times more likely to die as compared to children testing negative for influenza A(H1N1)pdm09.